Care needs profiles of Crohn’s disease patients and their associations with symptom clusters, post-traumatic growth, and family function: a latent profile analysis - Rongfei Duan; Wan Mei; Ming Lei; Danlei Chen; Ting Pan; Fang Kong; Yan Chen (BMC Gastroenterology)
Abstract Background and aims The care needs of patients with Crohn’s disease (CD) may be heterogeneous. This study aimed to explore the latent class of care needs of patients with CD and differences in their characteristics and to analyze the factors influencing the different latent classes. Methods A convenience sampling method was used to select 250 patients with CD who attended a tertiary-level hospital in Nanjing from August to November 2024 for the study. They were surveyed via the General Information Questionnaire, the Crohn’s Disease Care Needs Scale (CD-CNS), the Inflammatory Bowel Disease (IBD) Patient Symptom Clusters Assessment Scale, the Family Adaptability and Cohesion Scale (FACES), and the Post-traumatic Growth Inventory (PTGI). The latent classes of care needs of CD patients were identified via latent profile analysis (LPA), and the factors influencing their latent classes were analyzed via multiple logistic regression analyses. Results (1) The LPA results revealed that the care needs of CD patients were divided into three profiles as the best model fitting indicators: the “low-care-needs-adaptation group” (n = 96, 38.4%), the “moderate-care-needs-growth group” (n = 81, 32.4%), and the “high-care-needs-distress group” (n = 73, 29.2%). (2) Regression analyses revealed that current disease status, the presence of a stoma, symptom burden, family adaptability and cohesion, and post-traumatic growth (PTG) were influential factors in different latent classes. Conclusion There is significant heterogeneity in the care needs of CD patients. Care needs to focus on patients with high care needs and enhance their symptom management and psychological interventions to improve their PTG and reduce their disease burden.